2013
DOI: 10.1016/j.envres.2013.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Higher environmental relative moldiness index values measured in homes of adults with asthma, rhinitis, or both conditions

Abstract: Higher values of the Environmental Relative Moldiness Index (ERMI), a DNA-based method for quantifying indoor molds, have been associated with asthma in children. In this study, settled dust samples were collected from the homes of adults with asthma, rhinitis, or both conditions (n=139 homes) in Northern California. The ERMI values for these samples were compared to those from dust collected in homes from the same geographic region randomly selected as part of the 2006 American Healthy Home Survey (n=44). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Recently, the Shanghai group of CCHH reported that early furred pet‐keeping (Huang et al., ) and parental smoking (Liu et al., ) were risk factors for asthma and allergies among preschool children. Many studies have shown that dampness‐related problems (as evidenced by such signs as visible mold, visible damp stains, condensation on windows, and perceived mold odor) in the residence are significant risk factors for asthma and asthma‐related symptoms among children (Bornehag et al., , ; Fisk et al., ; Jaakkola et al., ; Mendell et al., ; Peat et al., ; Quansah et al., ; Sun and Sundell, ; Tischer et al., ; Weinmayr et al., ) and adults (Blanc et al., ; Brunekreef, ; Gunnbjörnsdottir et al., ; Norbäck et al., ). Bornehag et al., () have concluded that dampness in buildings appears to increase the risk of health effects (dry cough, wheeze, and asthma), especially in children.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the Shanghai group of CCHH reported that early furred pet‐keeping (Huang et al., ) and parental smoking (Liu et al., ) were risk factors for asthma and allergies among preschool children. Many studies have shown that dampness‐related problems (as evidenced by such signs as visible mold, visible damp stains, condensation on windows, and perceived mold odor) in the residence are significant risk factors for asthma and asthma‐related symptoms among children (Bornehag et al., , ; Fisk et al., ; Jaakkola et al., ; Mendell et al., ; Peat et al., ; Quansah et al., ; Sun and Sundell, ; Tischer et al., ; Weinmayr et al., ) and adults (Blanc et al., ; Brunekreef, ; Gunnbjörnsdottir et al., ; Norbäck et al., ). Bornehag et al., () have concluded that dampness in buildings appears to increase the risk of health effects (dry cough, wheeze, and asthma), especially in children.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have used mould‐specific quantitative PCR or the ERMI‐index in epidemiological studies on adult respiratory illness. One recent study found an association between ERMI values in home dust and asthma and rhinitis in adults . Moreover, few studies have investigated exacerbation of asthma from mould, assessed by the ERMI‐index.…”
mentioning
confidence: 99%
“…The average ERMI value in these Scottish homes of asthmatic adults was 5.3. In a study of asthmatic adults in the U.S., specifically California, the average ERMI value was 6.0 . No other study of adult asthmatics has utilized the ERMI metric.…”
Section: Discussionmentioning
confidence: 99%